2020
DOI: 10.3390/ma13133039
|View full text |Cite
|
Sign up to set email alerts
|

Mg-Zn-Ca Alloys for Hemostasis Clips for Vessel Ligation: In Vitro and In Vivo Studies of Their Degradation and Response

Abstract: To control the degradation rate of magnesium (Mg) alloys, chitosan (CHI) and L-glutamic acid (LGA) were used as coatings on Mg-Zn-Ca alloys via dip coating. In this study, either two or seven CHI/LGA layers were applied as a coating on Mg-2.8Zn-0.8Ca alloy (ZX31) and Mg-2.8Zn-0.8Ca hemostasis clips (ZX31 clips). The morphologies, compositions, and surface roughness of the specimens were characterized via scanning electron microscopy, Fourier transform infrared spectroscopy, and surface measurement devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The Mg-Zn-Ca-Y clip degraded completely after eight months. Coated Mg-2.8Zn-0.8Ca clips exhibited good biocompatibility when applied on rabbit uterine tubes for five weeks (Figure 7(a)) [419,420]. Notably, a pure-Mg clip was recognized as an innovative medical device by CFDA in 2018 (https://www.cmde.org.cn/xwdt/ shpgzgg/cxyxgsh/20180308143746124.html).…”
Section: Surgical Instruments For Hemostasis and Anastomosismentioning
confidence: 99%
See 1 more Smart Citation
“…The Mg-Zn-Ca-Y clip degraded completely after eight months. Coated Mg-2.8Zn-0.8Ca clips exhibited good biocompatibility when applied on rabbit uterine tubes for five weeks (Figure 7(a)) [419,420]. Notably, a pure-Mg clip was recognized as an innovative medical device by CFDA in 2018 (https://www.cmde.org.cn/xwdt/ shpgzgg/cxyxgsh/20180308143746124.html).…”
Section: Surgical Instruments For Hemostasis and Anastomosismentioning
confidence: 99%
“…Biological effects of Mg-based alloys on soft-tissue healing processes remain to be determined [143,426], and are highly dependent on the alloy composition and degradation nature [143]. Moreover, the degradation behaviour should be optimized to match the requirements of soft tissue repair [419].…”
Section: Surgical Instruments For Hemostasis and Anastomosismentioning
confidence: 99%
“…The advantageous properties could be attained only if the reinforcements are distributed homogeneously and not clustered in the matrix. According to the literature available [ 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 ], limited research has been performed on CNT-reinforced MMCs due to difficulties in fabricating and dispersion of CNTs in the matrix. Most studies investigated the fabrication methods such as the casting process and powder metallurgy for developing Mg-based alloy [ 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 ,…”
Section: Summary and Future Road Mapsmentioning
confidence: 99%
“…Lui et al developed a histological evaluation on Mg-Zn and observed the formation of new trabeculae surrounded by osteoblasts and osteoclasts, consequently, they observed mature bone tissue and lamellar bone, as characteristics fundamental for the consolidation of bone regeneration(57)(58). Chang et al carried out a histological study in animals observing good tolerance of the organism to metal ions, showing from an early stage a biocompatible response (59). Sarkar et al report proliferation of osteocytes and mononuclear cells in the medullary cavity of a rabbit femur, indicating the beginning of an important healing process from Zn-doped MgP (60)(61).…”
Section: Introductionmentioning
confidence: 99%